Applying the Macroscopic Kinetic Approach to Plasma Polymerization to the Plasma Surface Modification of Micropowders: Attempt of Correlating Powder Flowability and Plasma Process Parameters. Issue 3 (4th August 2015) - Giampietro, Vito Roberto; Roth, Christian; Gulas, Michal; Wood, Vanessa; Rudolf von Rohr, Philipp
Abstract : The flowability of micropowders can be improved by depositing a non‐continuous coating on the micropowder surface, which reduces the interparticle van der Waals forces causing cohesion of the native powder. Such a coating can be achieved via a plasma enhanced chemical vapor deposition in a tubular, inductively‐coupled RF glow‐discharge‐plasma reactor fed by plasma‐polymerizable gases. Here we systematically study the influence of user‐set plasma parameters of feed gas flow rate and plasma power on the resulting powder flowability. We find a quasi‐Arrhenius relation between flowability factor and energy delivered per mass of monomer W/FM . These findings demonstrate that flowability measurements can be used to study the plasma polymerization processes and as a metric to assess surface coatings of powders that are otherwise difficult to characterize by standard metrologies. Abstract : A fast plasma surface‐modification process with a tubular inductively‐coupled RF plasma reactor is utilized to improve the flowability of cohesive graphite micropowder by depositing a non‐continuous coating on the micropowder surface. A possible model based on a quasi‐Arrhenius equation correlating flowability and user‐set macroscopic plasma‐process parameters is proposed and discussed.